Mexico’s Long War on Drugs: Past and Present Failures of a Punitive Approach to Drugs - Gema Kloppe-Santamaria (Journal of Illicit Economies and Development, 2022)
The aim of this policy commentary is two-fold. First, to examine new historical research regarding the political, cultural, and social drivers informing the design and implementation of Mexico’s ‘war on drugs’ – a set of state policies centered on punitive and militarized responses towards the drug problem – during the first and second halves of the twentieth-century. Second, to analyze how the longer history of Mexico’s war on drugs can help us better understand this country’s enduring reliance on such punitive and militarized approaches despite the detrimental consequences these had and continue to have on citizens’ wellbeing and on the country’s democratic institutions.